Kemampuan Numerasi Peserta Didik Dalam Menyelesaikan Masalah Aljabar Ditinjau dari Gender - Astuti, Shiska Putri; Supiat, Supiat (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Numeracy is a skill in using various kinds of symbols related to basic mathematics. Numerical ability is important to be applied in teaching and learning activities in schools to be able to solve math problems. The purpose of this study was to determine the numeracy skills of male and female students in solving algebra problems. The research method uses qualitative methods with a descriptive approach. The subject taking technique used purposive sampling, the subject consisted of 3 male students and 3 female students. Data collection techniques in this study used written tests, interviews, and documentation. The results of this study indicate that the numeracy skills of male and female students with a high level of ability are able to analyze information, make and carry out solving steps, and are able to draw conclusions about answers correctly. Male students with moderate ability levels are able to make and carry out completion steps, and are able to make conclusions about answers correctly. Female students with moderate ability levels are able to make and carry out solving steps. Male students with a low level of ability are only able to make steps for completion but have not been able to take steps for completion, female students with low levels of ability are only able to analyze the information in the problem. Based on this analysis it can be concluded that the numeracy skills in solving algebra problems in male and female students are different.